Tax Reforms, Investor Sentiment and Closed-End Fund Performance - Kumar, Umesh Kumar (International Journal of Finance, 2022)
Purpose: Tax reforms have a significant impact on asset prices and shareholders' wealth. The Tax Cuts and Jobs Act 2017 (TCJA) reduces the tax obligations for both households and businesses. This paper investigates the relationship between closed-end funds performance and investor sentiment induced by tax reforms. Methodology: Two proxies of investor sentiment are used to measure the impact on closed-end fund (CEF) performance. Results: The results reveal that overall, tax reforms have a positive effect on the closed-end fund valuations. Institutional investors' sentiment takes a differential view from individual investors on CEF returns. Institutional investors' sentiment does not show a relationship with fund returns. Medium size CEFs benefit more from tax reforms. Unique Contribution to Theory, Policy and Practice: Despite mixed signals, the results suggest that TCJA has influenced the investors' sentiment resulting in excessive optimism.